Experimentally simulating warmer and wetter climate additively improves rangeland quality on the Tibetan Plateau. Issue 3 (12th January 2018) - Xu, Wei; Zhu, Mengyao; Zhang, Zhenhua; Ma, Zhiyuan; Liu, Huiying; Chen, Litong; Cao, Guangmin; Zhao, Xinquan; Schmid, Bernhard; He, Jin‐Sheng
Abstract: The vast expanses of rangeland on the Tibetan Plateau, which support the livelihood of c . 9.8 million local inhabitants, have experienced rapid climate warming over the past 50 years. At the same time, precipitation has increased in large parts of the Plateau but decreased in other parts, particularly in the northwest. These trends are predicted to continue into the future. However, their potential effects on rangeland quality remain unclear. We conducted a two‐factor field experiment in which we manipulated temperature (control or warming by 1.5–1.8°C) and precipitation (control or 50% reduction or increase in rainfall) in an alpine grassland on the northeastern Tibetan Plateau, starting in 2011. From 2014 to 2016, we measured forage production and community composition, and in 2015 forage quality (crude protein, cell‐soluble contents, hemicellulose, cellulose, lignin and digestibility) was represented by seven abundant species. Overall, warming did not change total forage production at plant community level, but increased legume production and decreased non‐legume forb production. Increased and reduced precipitation enhanced and decreased forage production by 18.2% and 12.9% respectively. Increased precipitation in particular increased grass and sedge production, but not legume production. Forage quality showed species‐specific responses to the simulated climate changes. At community level, warming and reduced precipitation improved forage quality, which were mainly caused by a shift in community composition towards more legumes, rather than the direct effects of simulated climate changes. Meanwhile, increased precipitation did not reduce forage quality, despite the precipitation‐induced increase in forage production. Integrating forage production and quality into nutrient production as a measure of rangeland quality, we found that warming and increased precipitation additively improved rangeland quality, while reduced precipitation decreased it. Synthesis and applications . Rangeland quality, an important ecosystem provisioning service, will benefit from a warmer climate on the Tibetan Plateau in the regions with a predicted increase in precipitation, but not in those regions where precipitation might be reduced in the future. We suggest management strategies, including reseeding native legumes, establishing sustainable pastures and assisting the exchange of harvested forage, to cope with the challenges posed by these different climate change scenarios. Abstract : Rangeland quality, an important ecosystem provisioning service, will benefit from a warmer climate on the Tibetan Plateau in the regions with a predicted increase in precipitation, but not in those regions where precipitation might be reduced in the future. We suggest management strategies, including reseeding native legumes, establishing sustainable pastures and assisting the exchange of harvested forage, to cope with the challenges posed by these different climate change scenarios.